2011
DOI: 10.1017/s0007114511006647
|View full text |Cite
|
Sign up to set email alerts
|

In vitrofermented nuts exhibit chemopreventive effects in HT29 colon cancer cells

Abstract: It is proven that nuts contain essential macro-and micronutrients, e.g. fatty acids, vitamins and dietary fibre (DF). Fermentation of DF by the gut microflora results in the formation of SCFA which are recognised for their chemopreventive potential, especially by influencing cell growth. However, little is known about cellular response to complex fermentation samples of nuts. Therefore, we prepared and analysed (pH, SCFA, bile acids, tocopherol, antioxidant capacity) fermentation supernatant (fs) fractions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
7
22
0
Order By: Relevance
“…These results are in line with former studies which have shown that the fermentation of dietary fiber or fiber-rich foods results in the formation of SCFA and concurrently in lower pH values [31,32]. Similar results have also been obtained by Lux et al [22], who applied different types of nuts to an in vitro simulated digestion. The marginal differences between the SCFA values in our study compared to those by Lux et al can be explained by the used feces matrix, which was obtained from different donors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in line with former studies which have shown that the fermentation of dietary fiber or fiber-rich foods results in the formation of SCFA and concurrently in lower pH values [31,32]. Similar results have also been obtained by Lux et al [22], who applied different types of nuts to an in vitro simulated digestion. The marginal differences between the SCFA values in our study compared to those by Lux et al can be explained by the used feces matrix, which was obtained from different donors.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the SCFA-mediated lowering of pH values in the FS might lead to reduced solubility of secondary BA as well as a reduction in 7α-dehydroxylase activity, which catalyzes the conversion of primary into secondary BA [50]. The results of the present study are in line with former studies, which have also shown a reduction in secondary BA concentrations upon in vitro fermentation of different dietary fiber sources [22,24,31,32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Butyrate could therefore be mainly responsible for growth inhibitory effects of macadamia FS observed in the present study. These results are in line with other studies demonstrating growth inhibition of LT97 colon adenoma [18] or HT29 colon carcinoma cells [28] by FS obtained from different raw nut varieties including macadamia. Growth inhibition of colon adenoma or cancer cells could also be shown for FS obtained from other dietary fiber rich sources such as bread [29] or wheat aleurone [30], respectively.…”
Section: Discussionsupporting
confidence: 93%